Comparing Translated Science Achievement Test Using Differential Item Functioning. - Ong, Saw Lan; Lee, Lay Wah (2006)
Malaysia was a former British colonial country. The Malaysian education system adopted the British Education system which consists of the primary, lorver secondary,upper secondary and post secondary.